Over 12% Efficiency Nonfullerene All‐Small‐Molecule Organic Solar Cells with Sequentially Evolved Multilength Scale Morphologies. Issue 12 (7th February 2019) - Gao, Ke; Jo, Sae Byeok; Shi, Xueliang; Nian, Li; Zhang, Ming; Kan, Yuanyuan; Lin, Francis; Kan, Bin; Xu, Bo; Rong, Qikun; Shui, Lingling; Liu, Feng; et al.
Abstract: In this paper, two near‐infrared absorbing molecules are successfully incorporated into nonfullerene‐based small‐molecule organic solar cells (NFSM‐OSCs) to achieve a very high power conversion efficiency (PCE) of 12.08%. This is achieved by tuning the sequentially evolved crystalline morphology through combined solvent additive and solvent vapor annealing, which mainly work on ZnP‐TBO and 6TIC, respectively. It not only helps improve the crystallinity of the ZnP‐TBO and 6TIC blend, but also forms multilength scale morphology to enhance charge mobility and charge extraction. Moreover, it simultaneously reduces the nongeminate recombination by effective charge delocalization. The resultant device performance shows remarkably enhanced fill factor and J sc . These result in a very respectable PCE, which is the highest among all NFSM‐OSCs and all small‐molecule binary solar cells reported so far. Abstract : Nonfullerene‐based small‐molecule organic solar cells with a new record efficiency of 12.08% are achieved by first incorporation of near‐infrared absorbing molecules and by tuning the sequentially evolved crystalline morphology. The improved crystallinity of both donor and acceptor materials facilitates the formation of multilength scale morphologies, which further enhance charge mobility and extraction, and reduce the nongeminate recombination.